LEGAL IMPLICATIONS OF REGULATORY PROVISIONS ARTICLE 10 VERSE (5) LAW NO. 46 OF 2009 CONCERNING THE CORRUPTION CRIMINAL COURT - Ahmad Fauzi; Abdul Madjid; Nurini Aprilianda; Prija Djatmika (UNISSULA, 2020)
The corruption criminal court is an institution that is given the authority to examine and decide corruption cases. The purpose of this study was to determine the juridical implications of the principle of the independence of the judicial power. This study uses a normative approach with quantitative analysis. The existence of a corruption court established on judicial power states that a special court can only be formed by a separate law. Then the corruption court is an institution that has the authority to examine and decide corruption cases. In its implementation, the composition of judges in the corruption court is divided into two, namely career judges and ad hoc judges. In its implementation, there are several things in the legislation that are contrary to the principle of independence of judicial power and violate the principle of freedom of judicial power, especially for ad hoc judges in the criminal court of corruption.